Synthesis, structural characterization and in vitro cytotoxicity of diorganotin complexes with schiff base ligands derived from3-hydroxy-2-naphthoylhydrazide - Mun, L.S.; Mun, L.K.; Nurestri, A.M.S.; Shin, S.K.; Hapipah, M.A. (2012)
A series of diorganotin complexes with Schiff base ligands, (E)-N'-(5-bromo-2-hydroxybenzylidene)-3-hydroxy-2-naphthohydrazide, H2L1, and (E)-N'-(5-chloro-2-hydroxybenzylidene)-3-hydroxy-2-naphthohydrazide, H2L2, were synthesized and characterized by elemental analysis, IR, 1H, 13C and 119Sn NMR spectroscopy. The molecular structures of the complexes, [(5-bromo-2-oxidobenzylidene)-3-hydroxy-2-naphthohydrazidato]di(o-chlorobenzyl)tin(IV) 6 and [(5-chloro-2-oxidobenzylidene)-3-hydroxy-2-naphthohydrazidato]dibutyltin(IV) 9, were determined through single-crystal X-ray diffraction and revealed a distorted trigonal-bipyramidal configuration. The in vitro cytotoxic activity of the Schiff bases and their diorganotin complexes was also evaluated against several human carcinoma cell lines, namely HT29 (human colon carcinoma cell line), SKOV-3 (human ovarian cancer cell line), MCF7 (hormone-dependent breast carcinoma cell line) and MRC5 (non-cancer human fibroblast cell line). [(5-Bromo-2-oxidobenzylidene)-3-hydroxy-2-naphthohydrazidato]dibutyltin(IV) 2 and [(5-bromo-2-oxidobenzylidene)-3-hydroxy-2-naphthohydrazidato]dibenzyltin(IV) 5 were the most active diorganotin complexes of H2L1 ligand. Among the diorganotin complexes of H2L2 ligand, [(5-chloro-2-oxidobenzylidene)-3-hydroxy-2-naphthohydrazidato]dicyclohexyltin(IV) 11 showed good cytotoxic activity against all the tested cell lines. As such, the above compounds can be considered agents with potential anticancer activities, and can therefore be investigated further in in vitro or in vivo anticancer studies. Copyright (c) 2012 John Wiley & Sons, Ltd.